Productivity Measurement Using the Objective Matrix (OMAX) on the PT XYZ Non Woven Production Floor - Arsyad Sumantika; Ganda Sirait (Formosa Journal of Applied Sciences, 2022)
Productivity is an absolute concern. This relates to the total performance in a company related to the level of efficiency and effectiveness. PT XYZ is a company that produces non-woven disposable clothes. However, in reality, often the targets set are not as expected by the company. The purpose of this study was to measure the productivity level of PT XYZ on non-woven machines. While the method used uses the Objective Matrix (OMAX) and data collection is carried out for 3 months, namely July to September 2022 on the production floor on non-woven machines. with an index value of 320, while in September it was at its lowest point with an index value of 180. This occurred with an increase in total products produced by PT XYZ but on the other hand there was a decrease in the number of hours worked by employees, labor, energy usage, number of hours when there is a breakdown of the machine and the product being repaired.